A REPAIR-REPLACE STRATEGY BASED ON USAGE RATE AND PRODUCT AGE UNDER TWO-DIMENSIONAL WARRANTY - IKA RINAWATI (NIM: 23407024), DYAH
When the manufacturer selling products with warranties, it causes additional costs (called warranty costs) to service any claims under warranty. Reducing warranty costs is an issue of great interest to manufactures. The three ways to reduce warranty costs i.e. improving product reliability, use of preventive maintenance and warranty servicing strategy. This research deals with a warranty servicing strategy for items sold with a two dimensional warranty where the region offered is relatively large. For instance, an automobile warranted for three years or 36.000 km, which come first. For repairable products sold with free repairable warranty (FRW), the manufacturer has the option of either repairing or replacing the failed item with a new one. In the strategy studied, the decision of repairing or replacing the failed item under warranty is based on its age at failure. Under the strategy, for failures with age being greater than or equal to threshold parameter will be rectified by replacement and all other failures under warranty will be repaired. This strategy is characterized by a threshold parameter which minimizes the expected warranty cost. Renewal-type equation is involved in the warranty cost model. The optimal parameter is sought by using numerical computation. An accelerated failure time (AFT) model is used to allow for the effect of usage rate on item degradation. Some numerical examples are given for the purposes of illustration.